Penerapan Metode Bercerita Dalam Penanaman Agama Islam di Taman Kanak-Kanak - Elvi Susanti (Yayasan Darusssalam Bengkulu, 2020)
The storytelling method is one thing that can encourage children's potential towards Islamic behavior and religion in kindergarten, The storytelling method is an interesting experience for children. By listening to stories, children are able to absorb the meaning and understand the emotions in them well. In the storytelling method, the teacher will give lessons orally. With the storytelling method, you will be happy to listen and listen to what the teacher says so that it will increase cognitive, emotional and expression abilities in young children. Several things made researchers choose this problem, namely 1) Islamic religious education is the foundation that needs to be given to children to learn about the Islamic religion. 2) One method that teachers can convey to children is the storytelling method. 3) the potential influence of the storytelling method on children's behavior. The method used is descriptive qualitative, where the methods used are interviews, observation and documentation with the subjects studied by teachers and students at Kartini Panorama Kindergarten Bengkulu. The results of the research carried out by the teacher will tell stories about Islamic figures such as stories about the Prophet Muhammad and the Prophet's companions using serial pictures, story books and dolls that are adapted to the teaching materials they want to do with the children.